Confidential print Borneo and Sulu 1889-1896 (Great Britain : Public Record Office, 1971)
Mengandungi utusan'Borneo protector';'Further correspondence respecting the affair of Borneo and Sulu 1889'; memorandum respecting proposed bases for a joint commission on the North Borneo Boundary';'Futher correspondence respecting the affair of Borneo and Sulu 1890-1896'.